Smartphone use after work mediates the link between organizational norm of connectivity and emotional exhaustion: Will workaholism make a difference?. (23rd July 2021) - Cheung, Yue Lok (Francis); Lun, Miu Chi (Vivian); Wang, Hai‐Jiang
Abstract: Using smartphone for work in off‐work hours has been associated with negative employee outcomes. We postulate that: (1) organizational norm of connectivity precedes employees' work‐related smartphone use after work, which predicts emotional exhaustion among employees; and (2) this process is moderated by employees' workaholism. We collected data from 399 full‐time employees who completed six online surveys over 3 workdays to test our hypotheses. Multilevel path analysis of these data revealed that organizational norm of connectivity was more strongly related to smartphone use after work among employees with high workaholism compared to those with low workaholism. However, smartphone use was more strongly related to emotional exhaustion among those with low workaholism compared to those with high workaholism. In total, the indirect effect of organizational norm of connectivity on emotional exhaustion through work‐related smartphone use after work was significant only for those with low workaholism. These findings highlight the role of organizational norm of connectivity and individual workaholism in the association of work‐related smartphone use after work and negative employee outcomes. We discussed the theoretical and practical implications of these findings.